2014
DOI: 10.1186/1471-2318-14-20
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses indicating pain and analgesic drug prescription in patients with dementia: a comparison to age- and sex-matched controls

Abstract: BackgroundThe evidence of undertreatment of pain in patients with dementia is inconsistent. This may largely be due to methodological differences and shortcomings of studies. In a large cohort of patients with incident dementia and age- and sex-matched controls we examined (1) how often they receive diagnoses indicating pain, (2) how often they receive analgesics and (3) in which agents and formulations.MethodsUsing health insurance claims data we identified 1,848 patients with a first diagnosis of dementia ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 42 publications
5
30
1
2
Order By: Relevance
“…One explanation might be the lack of serious interactions with other drugs or diseases compared to alternatives, an issue highly relevant in older patients using multiple drugs. Furthermore, it is well known that women receive more analgesics including metamizole than men, which was also found in our study. The large regional variations are also of interest.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…One explanation might be the lack of serious interactions with other drugs or diseases compared to alternatives, an issue highly relevant in older patients using multiple drugs. Furthermore, it is well known that women receive more analgesics including metamizole than men, which was also found in our study. The large regional variations are also of interest.…”
Section: Resultssupporting
confidence: 89%
“…We found that every 15th person in this German cohort received at least one prescription of metamizole with increasing prevalence with age. Other studies have also shown that metamizole is commonly prescribed in older persons including nursing home residents . One explanation might be the lack of serious interactions with other drugs or diseases compared to alternatives, an issue highly relevant in older patients using multiple drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the levels of care dependency indicating physical disabilities we also used the number of prescribed medications as a measure of health status like in a recent paper [26]. It has been shown that the number of distinct medications prescribed performed well as a predictor for health services utilization and mortality in older persons [27].…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies internationally have identified that pain is often substantially undertreated or untreated in geriatric patients (Daoust et al, 2014, Lukas et al, 2013, Morrison and Siu, 2000, Niruban et al, 2010, and that people with dementia are significantly less likely to receive analgesia than their cognitively intact counterparts (Closs et al, 2004, Hoffman et al, 2014, Morrison and Siu, 2000. There are particular issues with the management of pain for older patients in acute hospital settings (Atkinson and Almahdi, 2014, Carr et al, 2014, Chang et al, 2010, Lin et al, 2014, Niruban et al, 2010.…”
Section: Introductionmentioning
confidence: 99%